Potencial antioxidante dos bioativos presentes no óleo essencial de syzygium aromaticum l. na maturação in vitro de oócitos bovinos - Oliveira, Lhara Ricarliany Medeiros de (Universidade Federal Rural do Semi-Árido, 2021)
The Syzygium aromaticum essential oil (EOSA) has proven antioxidant activity. Nevertheless, because its bioactive substances are of different constitutions, it is necessary to apply bioguided studies to denote the greater antioxidant potential of EOSA, as well as to determine the ideal concentration. Thus, considering that the in vitro embryo production (IVEP) in cattle has variable efficiency, due to oxidative stress conditions, medium supplementation with these compounds may be an alternative to optimize the technique. Therefore, the aim was to evaluate the antioxidant potential of EOSA bioactives in bovine oocytes on nuclear and cytoplasmic maturation, viability of cumulus cells, levels of reactive oxygen species (ROS), levels of intracellular glutathione (GSH), mitochondrial membrane potential (ΔΨm), parthenogenetic embryonic development (Step 1); and different concentrations of the bioactive defined in the first step on the same parameters (Step 2). Oocytes were matured in the following supplements: EOSA20 (20 μg/mL EOSA), EUG (83 μM eugenol), β-CA (19 μM β-caryophyllene), ACT (12 μM acetyl acetate), CYS (100 μM cysteamine) and control (without antioxidant) for step 1; and E83 (83 μM eugenol), E100 (100 μM eugenol), E120 (120 μM eugenol), positive control (100 μM cysteamine) and negative control (without antioxidant) for step 2. In the step 1, all antioxidants were superior to the control for metaphase II (MII) rates (P < 0.05). Nevertheless, EUG, EOSA20 and CYS increased the extrusion rates of the first polar body (1PB, P < 0.05). Moreover, EUG showed a superior expansion and viability of the cumulus cells rates (P < 0.05). The rates of cytoplasmic maturation by mitochondrial distribution were higher in the EUG and ACT, and for the patterns of mitochondrial aggregation EUG, ACT and CYS stood out (P < 0.05). ROS levels were reduced and GSH levels were increased with EUG and CYS (P < 0.05). All groups showed lower levels of ΔΨm compared to the control and β-CA (P < 0.05). EUG, EOSA20 and CYS promoted higher rates of cleavage and embryonic quality, but EUG promoted a higher rate of blastocysts and structures with ≥ 8 cells in the cleavage (P < 0.05). Although the action of the other bioactive agents was positive, eugenol promoted the greatest activity and was used in the next step. In the step 2, the MII rates were higher in the E83 when compared other groups (P < 0.05). E83, E120 and the positive control increased the rates of 1PB (P < 0.05). E83 and positive control resulted in higher expansion and viability of cumulus cells (P < 0.05). Cytoplasmic maturation did not differ among groups with antioxidants, but mitochondrial aggregation stood out in E83 and positive control (P < 0.05). A lower ΔΨm was shown in the groups supplemented with antioxidants (P < 0.05). The ROS levels decreased with E83 and positive control, and the GSH levels increased with these and the E120 (P < 0.05). The cleavage rate and the number of hatched blastocysts was higher in the E83, as well as the embryonic quality (P < 0.05). In conclusion, although β-CA and ACT have positive antioxidant effects, 83 μM of eugenol added to IVM medium was the most interesting alternative among bioactive agents for maintaining the quality of bovine oocytes, as well as promoting the increase of subsequent embryonic development
Keywords: Produção in vitro de embriões; Homeostase oxidativa; Compostos fenólicos; In vitro embryo production; Oxidative homeostasis; Phenolic compounds; CIENCIAS AGRARIAS::MEDICINA VETERINARIA